2001
DOI: 10.1046/j.1365-3040.2001.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of atmospheric oxygen on leaf structure and starch deposition in Arabidopsis thaliana

Abstract: Plant culture in oxygen concentrations below ambient is known to stimulate vegetative growth, but apart from reports on increased leaf number and weight, little is known about development at subambient oxygen concentrations. Arabidopsis thaliana (L.) Heynh. (cv. Columbia) plants were grown full term in pre-mixed atmospheres with oxygen partial pressures of 2·5, 5·1, 10·1, 16·2, and 21·3 kPa O 2 , 0·035 kPa CO 2 and the balance nitrogen under continuous light. Fully expanded leaves were harvested and processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…The ratio of carboxylation to the oxygenation reaction (initiating photorespiration) strongly depends on the relative concentrations of CO 2 and O 2 , and on leaf temperature (Lambers et al, 1998). Because of competition between CO 2 and O 2 for Rubisco, the decreased partial pressure of O 2 at high elevations combined with the constant CO 2 partial pressure treatment likely reduces photorespiration, and could partly explain the large increase in A max observed with elevation here (Cornic, 1980;Sun, 1999;Ramonell, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…The ratio of carboxylation to the oxygenation reaction (initiating photorespiration) strongly depends on the relative concentrations of CO 2 and O 2 , and on leaf temperature (Lambers et al, 1998). Because of competition between CO 2 and O 2 for Rubisco, the decreased partial pressure of O 2 at high elevations combined with the constant CO 2 partial pressure treatment likely reduces photorespiration, and could partly explain the large increase in A max observed with elevation here (Cornic, 1980;Sun, 1999;Ramonell, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…Other symptoms may include aberrant deposition of starch grains and thickened cell walls (Ramonell et al, 2001). In a full life-cycle experiment with Brassica, Kuang et al (2000) found protein bodies that were 44% smaller (cross-sectional area).…”
Section: Discussionmentioning
confidence: 99%
“…We also looked for cell wall thickening, since this was seen in Arabidopsis leaves grown under reduced oxygen atmospheres and may be indicative of hypoxia (Ramonell et al, 2001). Figure 1 shows light micrographs of the seed.…”
Section: Seed Ultrastructurementioning
confidence: 99%
“…Along this line, there are other factors that could limit horizontal transfer into cpDNA, e.g., the double-membrane envelope surrounding the chloroplast is a more formidable barrier than the nuclear envelope. Also, mitochondria have a peculiar tendency for fusion-subdivision cycles that might increase their exposure to foreign DNA (38). Finally, there are examples of horizontally acquired introns, and recently, whole genes in the cpDNA of unicellular green algae (39,40).…”
Section: Discussionmentioning
confidence: 99%